IMPLEMENTASI METODE ANALITYCAL HIERARCHY PROCESS DALAM SISTEM PENUNJANG KEPUTUSAN HIMMSIUNIVERSITAS AMIKOM YOGYAKARTA - Febry Fidelia Prahastiwi; Agus Fatkhurohman (Jurnal Mantik Penusa)
This study proposes a decision support system for selecting HIMMSI administrators at Amikom University in Yogyakarta using the AHP method. Data obtained from observations and direct interviews with HIMMSI management. There are seven criteria used for assessment, namely: activeness (C1), responsibility (C2), creativity (C3), problem solving (C4), communicative (C5), public speaking skills (C6), and collaboration (C7) . This study applies the AHP method because each criterion has its own sub-criteria. The final results in this study in the form of ranking that can be printed by the admin while the user can only see it.